The Formation Of The Fairy Tale Genre In German Folklore - Khusanboy Madolimov (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2024)
This article examines the formation of the fairy tale (Märchen) genre in German folklore, emphasizing its distinction from myths, legends, and fables through formulaic openings, abstract settings, and typical characters. The Spinnstube (spinning room) tradition, where women told stories during evening work, is highlighted as a key performance context shaping the compact style, rhythmic structure, and memorability of tales. The study traces how mythological figures such as water nymphs, kobolds, and dwarfs were reinterpreted into moral-didactic roles under Christian influence. It also discusses the Grimms’ editorial practices, showing how oral variants were standardized into literary texts, while still reflecting the voices of narrators like Dorothea Viehmann. Drawing on the works of J. Zipes, M. Tatar, and other scholars, the article demonstrates how German fairy tales represent a synthesis of oral performance, social context, and Romantic literary scholarship